Ответ:
Д=9-8=1
х=2
х=1
(х-2)(х-1)/ (х-2)(х+2)=(х-1)/ (х+2)
Пошаговое объяснение:
Сократить дробь
Множитель
Разложить выражение на множители
Разложите выражение на множители
сократить дробь
ответ:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Д=9-8=1
х=2
х=1
(х-2)(х-1)/ (х-2)(х+2)=(х-1)/ (х+2)
Пошаговое объяснение:
Ответ:
Сократить дробь
Множитель
Разложить выражение на множители
Разложите выражение на множители
сократить дробь
ответ:![\frac{x-1}{x+2} \frac{x-1}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-1%7D%7Bx%2B2%7D)
Пошаговое объяснение: